Honey stimulates production of IL-8 chemokine by HT-29 intestinal epithelial cells - Siva Gowri Pathmanathan; Nurul Azmawati M.; Zarini I.; Wan Shahida WS; Anuar Sani (Nutrition Society of Malaysia, 2024)
Non-Indexed Publication